LEARNING PHYSICS USING RESEARCH-BASED MODELS WITH SCIENTIFIC APPROACHES TO IMPROVE STUDY PROBLEM SOLVING SKILL - Khairil Arif; Febri Yanto; Enjoni Enjoni (ATRIUM PENDIDIKAN BIOLOGI, 2021)
The development of learning tools is one of the abilities that must be possessed by teachers in each education unit in order to develop students' abilities in carrying out research-based learning. One tool that can support this goal is a learning tool based on research-based learning models with a scientific approach. The purpose of this study is to develop high school physics learning tools using a lerning based research model with a scientific approach with valid, practical and effective criteria. The type of research used is research and development. The results of research on the analysis of students obtained that class students have been able to develop the ability to solve problems. In the validity test obtained an average percentage of RPP 85.79%, an average handout of 85.68%, an average LKS of 86.20%, and an average rating of 87.50%. Practicality test results obtained an average percentage of the implementation of the RPP is 89.16%, the average teacher response questionnaire 90.83%, and the average student questionnaire response 88.33%. Furthermore, the results of the effectiveness test were obtained from an attitude competency assessment with an average of 86.50%, an average assessment of knowledge competence 87.50%, an average competency assessment of 89.50%. The research shows that the High School Physics Learning Tool uses a research-based learning model using a Scientific approach to the material characteristics of waves which are in the category of very valid, very practical, and very effective so that it is feasible to be applied in the learning process.